2022
DOI: 10.3390/su141811703
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing Approaches and Their Impact on Green Purchase Intentions: Mediating Role of Green Brand Image and Consumer Beliefs towards the Environment

Abstract: Today, customers see businesses as more than just profit seekers, they see them as organizations that are concerned about the well-being of their societies. Therefore, businesses have made sustainability a primary focus by implementing green marketing tactics to encourage consumers to buy green goods. The intention to buy green products was examined in relation to factors such as eco-labelling, green packaging and branding, and green products, premium, and pricing. This study analyses a model that incorporates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 108 publications
6
36
0
3
Order By: Relevance
“…To explore the interaction between attitudes towards NGOs and towards the brand, brand attitude is not only considered as a variable directly influencing the purchase intention of an eco-labelled product (H2) but also as an indirect influence [58]. Brand attitude has already been considered a mediating influence on the relationship between sustainability attributes and purchase intention [17][18][19][20]59].…”
Section: Brand Attitudementioning
confidence: 99%
“…To explore the interaction between attitudes towards NGOs and towards the brand, brand attitude is not only considered as a variable directly influencing the purchase intention of an eco-labelled product (H2) but also as an indirect influence [58]. Brand attitude has already been considered a mediating influence on the relationship between sustainability attributes and purchase intention [17][18][19][20]59].…”
Section: Brand Attitudementioning
confidence: 99%
“…Nowadays, marketers establish a distinction in the product packaging by modifying it to have a more environmentally friendly appeal. Prior studies have demonstrated that the use of green packaging and branding can have a favourable impact on customers' intention to make a purchase (Majeed et al, 2022). Various factors impact their selection, including the aesthetics of the packaging, the materials utilised, the biodegradability, recyclability, and the origin of the products (Wandosell et al, 2021).…”
Section: Green Packaging and Brandingmentioning
confidence: 99%
“…Customers may perceive the company's environmental initiatives differently, potentially leading them to believe that the company is making exaggerated claims or oversimplifying the complexity of its sustainable packaging strategy (Boz et al, 2020). Thus, it should be noted that although there is a growing demand for green packaging, which might potentially have a beneficial impact on consumer attitudes and purchase intentions, this may not hold true in other countries and markets (Jayasinghe, 2022;Majeed et al, 2022). A recent study conducted in Ghana and Malaysia revealed that eco-packaging does not significantly influence purchasing decisions in the country (Kong et al, 2014;Mahmoud et al, 2022) (Mahmoud et al, 2022).…”
Section: Green Packaging and Brandingmentioning
confidence: 99%
See 2 more Smart Citations